Possible Radiation-Induced Damage to the Molecular Structure of Wooden Artifacts Due to Micro-Computed Tomography, Handheld X-Ray Fluorescence, and X-Ray Photoelectron Spectroscopic Techniques. Issue 1 (20th May 2016) - Kozachuk, Madalena; Suda, Alexandra; Ellis, Lisa; Walzak, Mary; Biesinger, Mark; Macfie, Sheila; Hudson, Robert; Nelson, Andrew; Martin, Ronald; Heginbotham, Arlen
This study was undertaken to ascertain whether radiation produced by X-ray photoelectron spectroscopy (XPS), micro-computed tomography (μCT) and/or portable handheld X-ray fluorescence (XRF) equipment might damage wood artifacts during analysis. Changes at the molecular level were monitored by Fourier transform infrared (FTIR) analysis. No significant changes in FTIR spectra were observed as a result of μCT or handheld XRF analysis. No substantial changes in the collected FTIR spectra were observed when XPS analytical times on the order of minutes were used. However, XPS analysis collected over tens of hours did produce significant changes in the FTIR spectra.